2012
DOI: 10.1016/j.proche.2012.10.138
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating Bacteria With Functionalised Nanoporous Xerogels

Abstract: International audienceA new colorimetric and easy-to-use solid sensor for the detection of indole-producing bacteria is described. The sensor is a nanoporous matrix with tailored pores doped with a reactant, DMACA. The sensor turns rapidly from transparent to green-blue when exposed to metabolic indole coming from bacteria cultures, both in liquid and gas phases. An example of the discrimination between indole-positive (Eschericia coli) and indole-negative bacteria (Hafnia alvei), two important contaminants in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The xerogel was first ground and the trapped compound is extracted with methanol; the absorption spectrum of the alcoholic solution corresponds to that of indole in solution. To strengthen this hypothesis, the specific reaction of 4-(dimethyl-amino)-cinnamaldehyde, DMACA, with indole was applied, 7 by adding DMACA to the solution. The distinctive blue-green color observed can be attributed to the azafulvenium chloride salt, formed from the reaction of indole with DMACA, thus confirming our hypothesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The xerogel was first ground and the trapped compound is extracted with methanol; the absorption spectrum of the alcoholic solution corresponds to that of indole in solution. To strengthen this hypothesis, the specific reaction of 4-(dimethyl-amino)-cinnamaldehyde, DMACA, with indole was applied, 7 by adding DMACA to the solution. The distinctive blue-green color observed can be attributed to the azafulvenium chloride salt, formed from the reaction of indole with DMACA, thus confirming our hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…1a). It is based on the use of transparent porous matrices, whose functions are threefold: (i) the pore size is tailored to trap the volatile metabolite and the matrix acts as a sponge to concentrate the analyte, 7 (ii) the pore cavities are engineered to chemically change the metabolite and improve the detection and (iii) the transparent matrix allows a quantitative measurement of the metabolites with optical absorption measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of volatile compounds has been used for many years as part of bacterial identification systems, for example the imvic (indole, methyl red, Voges-Proskauer, and citrate) system which differentiates coliforms according to their production of indole, acetoin, and mixed acid fermentation products, in addition to their ability to metabolize citrate (MacFaddin 1980). This biochemical approach to the detection of microbial volatiles continues to the present day, for example functionalized nanoporous xerogels are currently being developed for detection of the presence of acetate and indole (Crunaire et al 2011).…”
Section: Microbial Voc Detection (Then and Now)mentioning
confidence: 99%
“…With a single monolithic and transparent xerogel disk whose diameter and thickness are 3 and 0.5 mm respectively (Fig. 4), Crunaire and Tran-Thi 33 have shown that these volatile organic pollutants can be trapped in the disk exposed to a small gas flow (100 mL min À1 ).…”
Section: Innovative Chemical Sensors 41 Hybrid Matrices With Tailored...mentioning
confidence: 99%